2021
DOI: 10.1080/11038128.2021.1950207
|View full text |Cite
|
Sign up to set email alerts
|

Exploring two subdimensions of participation, involvement and engagement: A scoping review

Abstract: Background: The conceptualisation of participation is an ongoing discussion with importance for measurement purposes. The aim of this study was to explore the two subjective subdimensions of participation, involvement and engagement. The purpose was related to measure development within the field of paediatric rehabilitation. Methods: In a scoping review, following the PRISMA-ScR, the databases MEDLINE, PubMed, Academic Research Complete, PsychINFO, and Business Source Complete were searched for publications t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…According to existing literature, observable involvement can be described as the observed partaking in an activity, for example, through focusing on a task. In contrast, non-observable involvement can be described as the feeling of inclusion, acceptance, and belonging as well as the felt engagement in an activity such as through flow or investment ( 5 , 8 , 73 , 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to existing literature, observable involvement can be described as the observed partaking in an activity, for example, through focusing on a task. In contrast, non-observable involvement can be described as the feeling of inclusion, acceptance, and belonging as well as the felt engagement in an activity such as through flow or investment ( 5 , 8 , 73 , 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…The notion of engagement as process refers to the fact that it is both dynamic and co-constructed between the practitioner and individual. 40 , 42 , 43 This highlights the role of the practitioner in achieving a state of engagement and challenges previous thinking which located “the problem” entirely with the “patient”. Furthermore, there has been a growing recognition of the potential impacts of the family, service context, and cultural and societal factors on engagement.…”
Section: Introductionmentioning
confidence: 94%
“…Role performance implies that the individual is executing and experiencing their specific role, such as being a student, mother, etc. [34]. This also can differentiate participation from activity [28,35].…”
Section: Plos Onementioning
confidence: 99%
“…A qualitative study based on an interview with disabled patients identified important aspects of participation such as active and meaningful engagement/being a part of choice and control [3]. Involvement and engagement are subjective subdimensions of participation often neglected in measuring participation [34]. Based on the definition, engagement comprises the individual's behavioural, cognitive, and affective investment during role performance [34].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation